Supporting Students' Movement Up the Staircase of Text Complexity. (1st March 2013) - Hiebert, Elfrieda H.
Abstract Standard 10 of the Common Core State Standards attends to students' capacity with complex text. This standard distinguishes the Common Core State Standards from previous standards documents. This article describes a process—the Text Complexity Multi‐Index (TCMI)—that supports teachers in studying texts to support their students in increasing capacity with complex text. The TCMI addresses the three prongs of the text complexity triad identified by the CCSS: quantitative, qualitative, and reader‐task. As teachers apply steps of the TCMI process, they become increasingly knowledgeable about the features of texts that can create challenges for students and those that provide the content of lessons that support students in reading increasingly more complex texts across their school careers.